Noise in agricultural machinery: Modernization and workers' health - Moraes, Stefani Refatti; Dias, Vilnei de Oliveira; Cornélio, Jhon Pablo Lima; Hitz, Maria Eduarda (Seven Editora, 2023)
The evolution of agricultural mechanization improved operational and productive performance, reducing human physical effort, and increasing productivity per area. However, the worker remains exposed to various occupational risks when operating an agricultural machine, whether physical, chemical, or biological, increasing the incidence of occupational diseases. The noise generated by agricultural operations is considered one of the main ergonomic factors harmful to the machinery operator and people close to the noise range, affecting not only hearing, but well-being and performance when carrying out work, increasing the possibility of accidents. In research carried out using a mechanized tractor-sprayer set with air assistance in the spray bars, as a way of evaluating the influence of implementing implements on the noise levels emitted by agricultural tractors, an increase in sound intensity was observed when air assistance was used. it was switched on, mainly, in places closer to the noise source, and when the tractor was operating at higher engine speeds. The effects of exposure to noise generated by machinery and agricultural implements are better perceived in the long run, when their effects become more severe. The modernization of the mechanization sector has made it possible to attenuate the noise perceived by operators using cabins, however, employees working in proximity are also exposed to sound emissions, making it essential to use personal protective equipment (PPE), such as ear protectors. DOI:https://doi.org/10.56238/interdiinovationscrese-077